Stressor Response Model for Tape Grass (Vallisneria americana) - Frank J. Mazzotti; Leonard G. Pearlstine; Robert H. Chamberlain; Melody J. Hunt; Tomma Barnes; Kevin Chartier; Donald DeAngelis (EDIS)
Circular 1524, a 22-page illustrated circular by Frank J. Mazzotti, Leonard G. Pearlstine, Robert H. Chamberlain, Melody J. Hunt, Tomma Barnes, Kevin Chartier, and Donald DeAngelis, is one of a suite of Caloosahatchee estuary models which are being considered together for Everglades restoration plan evaluation. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, January 2008.